Proceedings of the Third International Conference on Sustainable Innovation 2019 – Humanity, Education and Social Sciences (Ico 2019
DOI: 10.2991/icosihess-19.2019.5
|View full text |Cite
|
Sign up to set email alerts
|

ICT and Project-Based Learning in a Rural School: an EFL Context

Abstract: This paper presents a description of a technology-based English learning in an Indonesian context project completed by rural high school students. It employed a descriptive qualitative research method in a class consisting of 35 students. The data were collected from videotaped observations, interviews with participant representatives, and questionnaires administered to all participants. The project-based instruction (PBL) was implemented in five sessions, with videos uploaded to YouTube as the final product. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
4
5
0
Order By: Relevance
“…The majority of students responded that they became more creative as they could use digital tools and apps to explore and communicate their ideas in completing project work, similar to the previous studies (Bell, 2010;Haniah et al, 2021;Santhi et al, 2019;Sukerti & Susana, 2019). The digital English project craves students' creativity in providing informative and well-designed products.…”
Section: "Our Distant Learning and Project Work Can Be Facilitated In...supporting
confidence: 75%
See 1 more Smart Citation
“…The majority of students responded that they became more creative as they could use digital tools and apps to explore and communicate their ideas in completing project work, similar to the previous studies (Bell, 2010;Haniah et al, 2021;Santhi et al, 2019;Sukerti & Susana, 2019). The digital English project craves students' creativity in providing informative and well-designed products.…”
Section: "Our Distant Learning and Project Work Can Be Facilitated In...supporting
confidence: 75%
“…"There are still many new features that must be learned in the app that I use". (Q1S147) This is in line with Fathali et al (2020) and Santhi et al (2019) who said that students lacked knowledge about the technology and the skills to use it. Teachers have control over the usage of instructional tools (digital equipment) when they are utilized by them (Hamilton, 2018) but not when the tools are chosen and operated by the students themselves.…”
Section: Challenges Of Pbl With Technologysupporting
confidence: 73%
“…Students reported that their English level had improved through video presentations (Cowie & Sakui, 2018;El-Garawany, 2017;Kulsiri, 2018;Naqvi & Al Mahrooqi, 2016;Santhi, Suherdi, & Musthafa, 2019;Stanley & Zhang, 2018). Huang (2021) recorded statistically significant higher test scores from students after completing video tasks in the classroom.…”
Section: Building Efl Skills Through Video Presentationsmentioning
confidence: 99%
“…Cowie and Sakui (2018) raised another concern about teaching technology in the student's second language as a threshold level of English might be necessary. Santhi et al (2019) found that 13 out of 35 students had difficulties creating and editing the videos, indicating how technologically challenging the project could be. Another issue students faced was how to send their large video files through email (Miskam & Saidalvi, 2020).…”
Section: Building 21 St -Century Skills Through Video Presentationsmentioning
confidence: 99%
“…There are two studies that are relevant to this research and are used to support it. Santhi et al (2019) conducted a research study about ICT and PBL in a rural school. They investigated how the 35 students completed video project uploaded in YouTube.…”
Section: Introductionmentioning
confidence: 99%